A Comprehensive Study of Sternal Foramen in a Pakistani Cohort: Prevalence and Morphometric Analysis - Tasleem, Maria; Atta, Iram; Hina, Mohtasham; Tafweez, Raafea; Yousaf, Ayesha (Journal of Rawalpindi Medical College, 2025)
Objectives: This study aims to find the prevalence and morphometry of sternal foramen in the Pakistani population to prevent any potential cardiac complications and radiological or medicolegal misinterpretations. Materials & Methods: This study was conducted on 178 dry human sternum bones of unknown sex and age available at the bone bank of King Edward Medical University Lahore, Pakistan. All the bones were grossly inspected for the presence of foramen. To describe the exact location of foramen its distance from the right and left sternal border was measured. For the size of the foramen, its vertical and transverse diameter was taken. Results: The prevalence of foramen was found to be 7.3%. The foramina were round (53.8%) in shape, median (53.8%) in position and were located on body (61.5%). The average transverse diameter was found to be 3.08mm and the average vertical diameter was 2.83mm. Conclusion: This study provides valuable insights for cardiac surgeons, acupuncture specialists, forensic experts, and radiologists, helping them avoid potential complications that may arise from the lack of awareness of the sternal foramen. Key Words: Sternal Foramen, Medico-legal Significance, Acupuncture, Bone marrow biopsies